Structure, magnetic property and DNA cleavage ability of heterometal Mn2IIINi2II complex with ONO tridentate ligands - Ding, Y.; Xu, J.; Pan, Z.; Zhou., H.; Lou, Xia (Elsevier Science B.V., 2012)
A new hetero-tetranuclear complex [MnIII2NiII2(HL)2L2(OAc)2(CH3OH)2]CH3OH (1) has been synthesized and fully characterized, where H2L is N-(2-hydroxy-5-fluro-methylphenyl)-3-imine-2-propanol. The X-ray diffraction analysis of 1 shows that four metal ions as well as coordinated O atoms in one molecular unit exhibit a dicubane-like core with two missing vertexes. The extension of the magnetic exchange in 1 has been evaluated by means of a spin Hamiltonian, yielding the parameters of J1 = − 11.85 cm− 1, J2 = − 6.44 cm− 1 and J3 = 0.34 cm− 1, D = 2.26 cm− 1 and g = 2.12, assumed under same anisotropy D and g. And the DNA cleavage ability of 1 was also investigated.